Integrované mosty - Tej, Petr; Tej Petr (České vysoké učení technické v Praze, 2012)
Dissertation is focused on integral bridges, particularly on their transition areas, where interaction raises between the bridge structure and surrounding soil body. The work consists of several parts. In the first part is defined integral bridge and described its behaviour. It introduces solutions of transition areas for these type of bridges. There are also shown some faults of transient areas of integral bridges.The second part is devoted to deformations of concrete and there are introduced and compared several methods for calculation of creep and shrinkage of concrete. The third section deals with comparison of the total displacements of the three types of structures: reinforced concrete structure, prestressed structure, and steel concrete composite structure. The fourth and fifth sections deal with earth pressures. There are compared several methods of calculation of earth pressures, modules reaction forces on rests and modifying factors. The comparison is done for the model structure. The sixth and seventh section is devoted to the problem of extension of existing loading of transition areas by the additional variable load. It describes methods for calculating the increment of earth pressure at the end support. Here are also published graphs of the increase of earth pressures on bridge support opposite to the one having loading extension. In the eighth part is introduced the experiment. Earth pressures, deformation of soil body in the backfill area and compaction due to cyclic loading are measured on the experimental model body, that represents the segment of integral bridge construction located at the end supports area. Results and comparison with the theoretical part are mentioned in the ninth part. Tenth section is devoted to establishing (description) of proposal of design of thickness of the transition slab methodology. Eleventh part deals with the preparation of a measurement on a real structure.

Dissertation is focused on integral bridges, particularly on their transition areas, where interaction raises between the bridge structure and surrounding soil body. The work consists of several parts. In the first part is defined integral bridge and described its behaviour. It introduces solutions of transition areas for these type of bridges. There are also shown some faults of transient areas of integral bridges.The second part is devoted to deformations of concrete and there are introduced and compared several methods for calculation of creep and shrinkage of concrete. The third section deals with comparison of the total displacements of the three types of structures: reinforced concrete structure, prestressed structure, and steel concrete composite structure. The fourth and fifth sections deal with earth pressures. There are compared several methods of calculation of earth pressures, modules reaction forces on rests and modifying factors. The comparison is done for the model structure. The sixth and seventh section is devoted to the problem of extension of existing loading of transition areas by the additional variable load. It describes methods for calculating the increment of earth pressure at the end support. Here are also published graphs of the increase of earth pressures on bridge support opposite to the one having loading extension. In the eighth part is introduced the experiment. Earth pressures, deformation of soil body in the backfill area and compaction due to cyclic loading are measured on the experimental model body, that represents the segment of integral bridge construction located at the end supports area. Results and comparison with the theoretical part are mentioned in the ninth part. Tenth section is devoted to establishing (description) of proposal of design of thickness of the transition slab methodology. Eleventh part deals with the preparation of a measurement on a real structure.
Integral bridges
Keywords: Integrované mosty, přechodová oblast, dotvarování betonu, smršťování betonu, zemní tlaky, zásyp, přechodová deska, podpěra, zemní těleso, Integral bridges, transition zore, creep of concrete, shrinkage of concrete, Earth pressures backfill, transition slab, support, soil structure